Hak dan kewajiban karyawan serta perusahaan: Sebuah tinjauan literatur - Kusuma, Avicenna Raihan (Maliki Interdisciplinary Journal, 2024)
This study aims to analyse the fulfilment of the rights and obligations of employees and companies within the framework of business ethics, particularly during the COVID-19 pandemic. Through the Systematic Literature Review (SLR) method, this study evaluates the literature that addresses the implementation of employee rights and company obligations between 2019-2024. The results show that companies are taking varied policies such as temporary layoffs and daily wage payments to cope with the impact of the pandemic. In addition, employees in various sectors continue to show high dedication despite facing discrepancies related to working hours and compensation. This study reinforces the importance of balancing rights and obligations in maintaining harmonious and productive working relationships in the midst of a crisis.